Knowledge, attitude, school support, motivation and use of contextual teaching among secondary school agriculture teachers in Malaysia - Abdul Latir, Siti Shuhaidah (2013)
Agriculture education is more than presenting a material as agriculture sector is becoming more technological, specialized and efficient. Agriculture science teachers face the slow adjustment of agricultural education programs and problem in choosing effective teaching and instructional strategies. Teachers’ responsibility as producers, seekers, and disseminators of knowledge increases to add facts and routine in students’ learning effectively. There is a need of agriculture science teacher to use different teaching approaches such as contextual teaching to improve previous teaching practice which only accentuates on students’ knowledge transfer for examination preparation thus allows students to connect education with their life. The purpose of this study is to identify the relationship between perceived knowledge, attitude, perceived school support, motivation and perceived use of contextual teaching among secondary school agriculture teachers. This study uses aquantitative approach with mail as a method for data collection. The instrument has been developed based from previous studies to measure perceived knowledge, attitude, perceived school support, motivation and perceived use of contextual teaching among secondary school agriculture teachers. The subjects of this study were drawn randomly to make a sample of 280 secondary school agriculture teachers in Malaysia. Results have shown that secondary school agriculture teachers have moderate level of perceived knowledge and positive attitude towards contextual teaching. Secondary school agriculture teachers have high level of perceived school support and they have moderate level of motivation towards contextual teaching. Results also show that secondary school agriculture teachers have high level of perceived use of contextual teaching. The result of this study shows there was a significant relationship between secondary school agriculture teachers’ perceived knowledge, attitude, perceived school support, motivation, and perceived use of contextual teaching. Teachers’ perceived use of contextual teaching among secondary school agriculture teachers were high and their knowledge, attitude, perceived school support and motivation contribute mostly in their application of contextual teaching in their classroom practices. The continuous use of contextual teaching will benefit students and school generally because contextual teaching is an effective teaching approach that prepares student to enter workplace and becoming an expert human capital for the country.